"It Might Actually Work This Time": Benefits and Barriers to Adapted 12-Step Facilitation Therapy and Mutual-Help Group Attendance From the Perspective of Dually Diagnosed Individuals. Issue 3 (July 2015) - Hagler, Kylee J.; Rice, Samara L.; Muñoz, Rosa E.; Salvador, Julie G.; Forcehimes, Alyssa A.; Bogenschutz, Michael P.
Abstract : Abstract: Most U.S. healthcare professionals encourage mutual-help group involvement as an adjunct to treatment or aftercare for individuals with substance use disorders, yet there are multiple challenges in engaging in these community groups. Dually diagnosed individuals (DDIs) may face additional challenges in affiliating with mutual-help groups. Twelve-step facilitation for DDIs (TSF-DD), a manualized treatment to facilitate mutual-help group involvement, was developed to help patients engage in Double Trouble in Recovery (DTR), a mutual-help group tailored to DDIs. Given the promising role that TSF-DD and DTR may have for increasing abstinence while managing psychiatric symptoms, the aim of the current study was to systematically examine reasons for TSF-DD and DTR attendance from the perspective of DDIs using focus group data. Participants were a subset ( n = 15) of individuals diagnosed with an alcohol use disorder as well as a major depressive, bipolar, or psychotic disorder who participated in a parent study testing the efficacy of TSF-DD for increasing mutual-help group involvement and reducing alcohol use. Analyses of focus group data revealed that participants construed DTR and TSF-DD as helpful tools in the understanding and management of their disorders. Relative to other mutual-help groups in which participants reported feeling ostracized because of their dual diagnoses, participants reported that it was beneficial to learn about dual disorders in a safe and accepting environment. Participants also expressed aspects that they disliked. Results from this study yield helpful empirical recommendations to healthcare professionals seeking to increase DDIs' participation in DTR or other mutual-help groups.